Research on benzene, toluene and dimethylbenzene detection based on a cataluminescence sensor. (17th May 2013) - Sun, Yan; Cao, Xiaoan; Liu, Yonghui; Wang, Nijing; He, Ruiwen
ABSTRACT We present a sensitive and quick way to determine benzene, toluene and dimethylbenzene (BTEX) in air, applying a cataluminescence (CTL) sensor based on a nano‐sized composite material, γ‐Al2O3/PtO2. The factors that affect the sensor's performance were studied, including the sensing material, temperature, rate of air carrier and wavelength. It was shown that when Pt accounted for 0.2% of the sensing material, the rate of the air carrier that carries target gas was 450 mL/min, the determination wavelength was 400 nm and temperature was 236°C, this sensor showed the best CTL intensity to BTEX. In addition, the CTL intensity had a high linear relation with the concentration of BTEX, with a linear range from 0.5 to 100 mL/m3, and a detection limit 0.22 mL/m3. This nano‐sized material had a quick response within 1.5 s, short recovery time within 1 min and a long lifetime, showing good potential for a variety of applications. Copyright © 2013 John Wiley & Sons, Ltd.